ANALISIS SISTEM PENUNJANG KEPUTUSAN PENENTUAN MASJID TERBAIK SEKOTA MAKASSAR MENGGUNAKAN METODE PREFERENCE SELECTION INDEX (PSI) - Fachrie Rizaldy, Muh; Satriawaty Mallu (Nusantara Hasana Journal, 2025)
Analysis of the Decision Support System for Determining the Best Mosque in the City of Makassar Using the Preference Selection Index (PSI) Method is a system created with the aim of assisting the Regional Office of the Ministry of Religion of South Sulawesi Province to make decisions regarding the determination of the best Mosque in the City of Makassar. The best mosque is a mosque that is well managed as the function of the mosque is not only as a place of prayer, but the mosque is also a place to study and develop the economy of Muslims. Based on these problems, a good mosque management system is needed so that it can be an example for other mosques. The Preference Selection Index (PSI) method can answer the problem of determining the mosque with the best management in Makassar City. The Preference Selection Index (PSI) method can solve multi-criteria decision making (MCDM) and does not need to determine the relative importance between attributes. In fact, there is no need to compute attribute weights involved in decision making in this method. It is hoped that this application will be useful for the South Sulawesi Province Ministry of Religion Regional Office to obtain information on the best mosques in the Makassar City area and make it easier to determine the best mosque in Makassar City.